Pengaruh Efektivitas Pelatihan terhadap Kinerja Pegawai dengan Kompetensi Soft Skill sebagai Variabel Mediasi: Studi pada Peserta Pelatihan Di PPSDM Kemendikdasmen - Cahayani Islamiati Putri; Eisha Lataruva (Faculty of Economics and Business Diponegoro University, 2026)
This study aims to examine the effect of training effectiveness on employee performance with soft skill competency as a mediating variable. The study was conducted at PPSDM of the Ministry of Primary and Secondary Education involving 150 employees who had participated in training programs. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that training effectiveness has a positive and significant effect on soft skill competency. Furthermore, soft skill competency significantly improves employee performance. However, the direct effect of training effectiveness on employee performance tends to be weaker compared to the indirect effect. The mediation test confirms that soft skill competency significantly mediates the relationship between training effectiveness and employee performance. These findings emphasize that improving employee performance in public sector organizations can be achieved more effectively through strengthening soft skill competency as an internal mechanism in transferring training outcomes into workplace practices.